2021
DOI: 10.1007/s11276-021-02670-7
|View full text |Cite
|
Sign up to set email alerts
|

Activity recognition of FMCW radar human signatures using tower convolutional neural networks

Abstract: Human activity recognition has become an obligatory necessity in day to day life and possible solutions can be provided with the technological advancement of sensing field. Radar based sensing with its unbeatable unique features has been a promising solution for identifying and distinguishing human activities in recent years. The ascent of loss of life among elderly people in care homes during COVID-19 is mainly due to poor monitoring services, that was not able to track their daily life activities. This has e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…When implementing HAR using radar sensors, the MFFNs can be divided into featurelevel fusion networks [28][29][30][31][32][33][34][35] and decision-level fusion networks [36][37][38]. Feature-level fusion methods extract features from multiple inputs and combine them to create an even more comprehensive and richer feature representation.…”
Section: Har Based On Multi-domain Feature Fusion Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When implementing HAR using radar sensors, the MFFNs can be divided into featurelevel fusion networks [28][29][30][31][32][33][34][35] and decision-level fusion networks [36][37][38]. Feature-level fusion methods extract features from multiple inputs and combine them to create an even more comprehensive and richer feature representation.…”
Section: Har Based On Multi-domain Feature Fusion Methodsmentioning
confidence: 99%
“…Feature-level fusion methods extract features from multiple inputs and combine them to create an even more comprehensive and richer feature representation. For example, simple stitching operations on features [29][30][31][32][33][34][35] and feature fusion summation operations [28] are the most common methods.…”
Section: Har Based On Multi-domain Feature Fusion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way of providing multi-domain radar to a CNN features extractor is presented by Helen et al [142] where a tower CNN consisting of parallel input layer was used in their work.…”
Section: Cnn Based Classifiersmentioning
confidence: 99%
“…Another approach to gait analysis using MDR utilized trunk movement to estimate biomechanical gait parameters instead of the conventional leg-movement-based method [14]. Changes in leg positions relative to the radar make the extraction of ankle-echoes challenging, especially in practical conditions that do not involve walking on a treadmill [15][16][17]. Saho and colleagues demonstrated that the novel trunk method enables the estimation of the swing and stance times and that the inclusive trunk and leg-based method improves the accuracy of gait estimations [14].…”
Section: Preventing Musculoskeletal Injuriesmentioning
confidence: 99%